2013
DOI: 10.1007/s13204-013-0274-1
|View full text |Cite
|
Sign up to set email alerts
|

Group analysis and numerical computation of magneto-convective non-Newtonian nanofluid slip flow from a permeable stretching sheet

Abstract: Two-dimensional magnetohydrodynamic boundary layer flow of non-Newtonian power-law nanofluids past a linearly stretching sheet with a linear hydrodynamic slip boundary condition is investigated numerically. The non-Newtonian nanofluid model incorporates the effects of Brownian motion and thermophoresis. Similarity transformations and corresponding similarity equations of the transport equations are derived via a linear group of transformations. The transformed equations are solved numerically using Runge-Kutta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…viscoelastic liquids (Bég et al. [46]), micropolar biopolymers (Bég et al [47]) and power-law shear thinning/thickening nanofluids (Uddin et al [37]), and will be communicated imminently. Tables Table 1 Comparison of values of   Table 2 Values of   …”
Section:  mentioning
confidence: 99%
“…viscoelastic liquids (Bég et al. [46]), micropolar biopolymers (Bég et al [47]) and power-law shear thinning/thickening nanofluids (Uddin et al [37]), and will be communicated imminently. Tables Table 1 Comparison of values of   Table 2 Values of   …”
Section:  mentioning
confidence: 99%
“…Velocity, temperature as well as concentration rises with convective heating parameter. Also, Uddin et al [21] investigated non-Newtonian nanofluid slip flow from a permeable stretching sheet. Their result showed that skin friction factor has a significant effect on the flow properties of Nan fluid.…”
Section: Introductionmentioning
confidence: 99%
“…with substituting f , ,  from equations(24)(25)(26) into equations(21)(22)(23) and some simplification and rearranging based on powers of p-terms, we have:…”
mentioning
confidence: 99%
“…10 Efforts in this direction have grown in the past few years. Uddin et al 25 employed an Ostwald-deWaele power-law model for nanofluid convection flows in porous media with multi-physical effects and also used the MAPLE software. Goyal and Bhargava 26 used a Reiner-Rivlin viscoelastic nanofluid model and a finite element code to study Crane stretching dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In the present thermofluid mechanical simulations, boundary layer theory is adopted owing to the excellent ability of this approach in capturing near-wall flow characteristics. The transformed boundary layer equations are solved using MAPLE shooting algorithms 25 and the influence of the bioconvection Lewis number, Peclet number, bioconvection Rayleigh number, power law rheological index and nanofluid parameters on heat, mass and momentum characteristics are explored in detail.…”
Section: Introductionmentioning
confidence: 99%